Gathering local ecological knowledge to augment scientific and management understanding of a living coastal resource: The case of Oregon’s nearshore groundfish trawl fishery - Sjostrom, Anja J.C.; Ciannelli, Lorenzo; Conway, Flaxen; Wakefield, W. Waldo (Marine policy, 2021)
Globally, coastal nearshore regions are an intersecting point for human and biological productivity, often serving as hotspots for subsistence, commercial, and recreational fishing activities. Despite this, many nearshore areas remain poorly understood, monitored or managed. This case study examined the nearshore sector of Oregon’s groundfish trawl fishery, which exists in shallow estuarine and continental shelf habitats common along the West Coast of North America; areas that are important for early life history stages of many commercial and recreational fisheries. The West Coast groundfish fishery includes over 90 different species, 40 of which occur within Oregon’s nearshore (here defined as the portion of the shelf extending seaward to a water depth of 200 m). The very shallow portions of the Oregon Coast (the area of the shelf inshore of 55 m) have been subject to limited scientific survey monitoring, and much of the details of the ecology, health, and processes in these habitats remain poorly understood. The utilization of the nearshore region by the commercial groundfish trawl fleet is also minimally documented despite the fact that experiential knowledge (local ecological knowledge [LEK]; trawl logbooks, fish tickets, interviews) exists. This research explored the capacity of capturing LEK sources to inform and enhance understanding of the drivers of effort and the vitality of nearshore fishery resources. Our approach used statistical analysis and mapping of nearshore trawl effort from 1981 to 2017 and gathered semi-structured interviews of intergenerational fishermen to bolster data-poor areas. Insights provided by sampling strategies and historical to current knowledge of access to groundfish assemblages provide informed baselines for future management. Spatial mapping results revealed a decline in trawl effort on the Oregon continental shelf thought time. Logbook and interview data assessment illuminated market and ecological drivers of fishing behavior as well as a unique sector of the groundfish fleet in Oregon: the beach fleet, with unique market and socio-economic challenges. Findings indicate a mixed-methods approach can provide a more thorough assessment of long-term interest in Oregon’s nearshore groundfish fishery. Ensuring better understanding of coastal interfacing regions such as Oregon’s nearshore insights potential for better conservation and utilization of marine resources and improved monitoring in resource limited management contexts. •Insights into Long-term trends in commercial fisheries emerge from social and ecological analysis.•LEK may offer detail for areas of low fisheries-independent sampling.•Mixed-method LEK from logbooks, fish tickets, and long-form interviews that supports stakeholder engagement.•Stakeholder engaged research may facilitate progress in ecosystem-based management.